Dietary intake of total vegetable, fruit, cereal, soluble and insoluble fiber and risk of all-cause, cardiovascular, and cancer mortality: systematic review and dose–response meta-analysis of prospective cohort studies - Yao, Feifei; Ma, Jianping; Cui, Yong; Huang, Cuihong; Lu, Ruiqi; Hu, Fulan; Zhu, Xiaoming; Qin, Pei (Frontiers in Nutrition, 2023)
Objectives To conduct a systematic review and meta-analysis of prospective cohort studies to investigate the association between total, vegetable, fruit, cereal, soluble and insoluble fiber intake and risk of all causes, cardiovascular disease (CVD), and cancer mortality and quantitatively assess the dose–response relation. Methods Eligible studies were identified by searching PubMed, Embase and Web of science before August 2023. Random effects models were used to calculate summary relative risk (RR) and 95% confidence intervals (CI) and restricted cubic splines to model the linear/non-linear association. Results The summary RR for all-cause, CVD and cancer mortality of dietary fiber was 0.90 (95% CI: 0.86,0.93), 0.87 (0.84,0.91), 0.91 (0.88,0.93), respectively. Significant association was observed for all-cause and CVD mortality with fruit, vegetable cereal and soluble fiber intake and cancer mortality with cereal fiber intake. No significant association was found for insoluble fiber, vegetable or fruit fiber intake and cancer mortality. Dose-response analysis showed a significant non-linear relation of dietary fiber intake with all-cause mortality, and linear relation for others. Conclusions Higher dietary fiber including different type and food sources of fiber intake were associated with lower risk of mortality. Our findings provide more comprehensive evidence on dietary fiber intake with mortality. Systematic review registration https://www.crd.york.ac.uk/prospero, identifier: CRD42022338837.